2010
DOI: 10.1007/s11195-010-9188-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Function in Patients with Gynecologic Cancer and Evidence-Based Nursing Interventions

Abstract: Sexual health is the integrity of somatic, intellectual, mental, emotional and social aspects of any individual. The cancer causes higher rates of sexuality related problems than other chronic diseases. Both the cancer diagnosis and the methods of treatment such as organ excision, radiotherapy, chemotherapy, the usage of hormones and cytostatic negatively affect the women's sexuality. Some models are used for diagnosing sexual dysfunction. These models are ALARM model, Kaplan model, Triphasic model, PLISSIT mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Constantly declining sexual desire and libido are among the most common problems. The symptoms leading to changes in body image, fatigue, nausea, vomiting, pain, intense stress and physical weakness were blamed for causing reductions in sexual desire [16]. During the study interviews, the women stated that problems associated with cancer treatment, such as hair loss, weight gain, and nausea, affected their external appearance in a negative manner.…”
Section: Discussionmentioning
confidence: 99%
“…Constantly declining sexual desire and libido are among the most common problems. The symptoms leading to changes in body image, fatigue, nausea, vomiting, pain, intense stress and physical weakness were blamed for causing reductions in sexual desire [16]. During the study interviews, the women stated that problems associated with cancer treatment, such as hair loss, weight gain, and nausea, affected their external appearance in a negative manner.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from cultural ones, many factors prevent nurses from evaluating the sexual health of patients and providing counseling to them (Krebs, 2008;Hordern, 2008;Algier and Sultan, 2008;Pınar, 2010;Gölbaşı and Evcili, 2013). Even though sexual counseling is known as an important part of nursing care, many studies report that nurses have difficulties in Umran Oskay et al dealing with this issue (Gordon, 1982;Shell, 2007;Julien et al, 2010;Oskay et al, 2011;Chun, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers are responsible for providing information and practical care so they should acknowledge patients' competency knowledge on disease and treatment, and they should possess effective communication skills and understanding of women with CC. 9,11,12 Previous studies have reported that QOL was lower in ACC-PT post-treatment compared to that of other women. [2][3][4]13 PC is one of health delivery services that support symptom management, symptom control, and QOL of post-treatment cervical cancer patients (PTCC-PT).…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to promote QOL for the PTCC-PT depending on multidimensional factors, including patients' dimensional factors and PC dimensional factors that enhance patients' self-management behaviors to reduce physical, mental, and social health problems. Patients' dimensional factors investigated in this study included demographic factors (age of the patients 9,18 , social support 4,5,19 , and patients' self-management) 7,12,15,20 , as well as medical factors (the stage of disease 13 , radiation therapy/ combination of radiation therapy and chemotherapy (RT/CCRT) 9,21 , and comorbidities 3 ). PC dimensional factors included model of care 22,23 , provider competence 7 , and provider support.…”
Section: Introductionmentioning
confidence: 99%